З ІСТОРІЇ БЛАГОДІЙНИХ ІНСТИТУЦІЙ М. ЧЕРНІВЦІ (НА МАТЕРІАЛІ ІСТОРІЇ ЗАКЛАДІВ ЗА СУЧАСНОЮ АДРЕСОЮ ВУЛ. АКСЕНИНА, 6) - Anistratenko, Antonina; Mendel, Anton (Aktualʹnì pitannâ suspìlʹnih nauk ta ìstorìï medicini (Online), 2018)
The article considers the main stages of the history of the formation and further development one of the most remarkable charitable institutions in Chernivtsi and Bukovina region. The aim of the article is to study the main stages of the formation and development of charitable institutions at the address: Aksenina Str., 6, it’s features and activities in the contexts of different countries and a difficult way in the XX – XXI centuries period. Authors pay attention also to the transition from a civil to a sovereign support model and social changes in educational processes. Consideration of the educational and future rehabilitation work development within the walls of institution, shows the evolution of views on solving problems of children who have sensory disabilities. During the work on the article, such methods were used: the system historical analysis method, the method of historical unity, the methods of synthesis and classification, the method of investigating archival documents. Scientific novelty is due to the fact that this topic was first studied scientifically, in the course of which was found a majority of previously unexplored documents, which according to the times of the Austrian empire, Romania and the USSR were introduced to scientific treatment. Proceeding from the work carried out, it is possible to draw a number of such conclusions: in the course of the study, the formation and further activity of the institutions at the current address Aksenina Str., 6, the evolution of educational, upbringing and rehabilitation work within the walls of institution and views on the problems of institutional pupils; the contribution to the work of institutions of different teaching staffs, the succession of which has been steadily changing under the influence of the historical realities of Bukovina, has been assessed, the impact of complex historical processes on the development of institutions has been examined.